التدخل الإنساني العراق: أنموذجا - منصور، سهير رفعت (الجامعة العراقية - مركز البحوث والدراسات الإسلامية, 2021)
إن تطور المجتمعات البشرية ونشؤ قواعد دولية لتعامل بين الدول جعلت موضوع الحماية مسألة قانونية دولية، إلا أن تذرع الدول بحماية حقوق الإنسان لتدخل في سيادة الدول لخدمة مصالح سياسية أو اقتصادية على حساب الدول الأقل منها قوة، جعلت مفهوم التدخل الإنساني يقاس بمكيالين وأصبحت الدول منهوبة الثروات تحت مسمى (الإنسانية وحقوق الإنسان). The development of human societies and the emergence of international rules for dealings and relationships among the states, it makes the subject of protection as an international legal issue, but some states invoke human rights protection to interfere in the sovereignty of stat to serve political or economic interests at the expense of the least powerful concept of humanitarian intervention measured by two measures and the weath countries are robbed under the name (humanity and human rights).
Keywords: التدخل الإنساني -- القانون الدولي الإنساني -- حقوق الإنسان -- العلاقات الدولية